Electrolyte for high-voltage-resistant aluminum electrolytic capacitor and preparation method thereof

Through polymerization reaction and ultrasonic dispersion technology, combined with pulse electric field and microwave processing, an electrolyte for high-voltage resistant aluminum electrolytic capacitors was prepared, which solved the problem of poor performance of existing electrolytes under high pressure and achieved high performance and low performance The cost of electrolyte preparation meets the safety and reliability requirements of modern electronic products.

CN119208019APending Publication Date: 2024-12-27ANHUI ZEHONG PLASTIC IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411643007.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing electrolyte for aluminum electrolytic capacitors has poor performance under high voltage, which can easily lead to flash fire and capacitor failure, and is relatively expensive, making it difficult to meet the high requirements of modern electronic products for safety and reliability.

Method used

Polymerization reaction is carried out using acrylic acid, hydroxyethyl methacrylate, butadiene and methacrylic acid as monomers, combining mannitol, ammonium dodenamic acid and 1-hydroxyethyl-3-methylimidazole tetrafluoroborate , a kind of resistant silicon nanomaterial was prepared by using bis(2,2,2-trifluoroethyl) carbonate and diethylene glycol butyl ether as solvents, and polyvinyl alcohol and porous silicon nanomaterials were added under pulsed electric field and microwave irradiation conditions. High voltage electrolyte.

Benefits of technology

It significantly improves the high-voltage resistance and flash fire voltage of the electrolyte, avoids the water generation problem caused by the esterification reaction of boric acid and glycol, improves the conductivity and overall performance of the electrolyte, and meets the electrolytics of aluminum by modern electronic products. High performance requirements for capacitors.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an electrolyte for a high-voltage-resistant aluminum electrolytic capacitor and a preparation method thereof, and the method comprises the steps: firstly, taking acrylic acid, hydroxyethyl methylacrylate, butadiene and methacrylic acid as monomers, and carrying out a polymerization reaction to obtain a polymer; then, the polymer, mannitol and ammonium dodecanedioate are ultrasonically dispersed in 1-hydroxyethyl-3-methylimidazolium tetrafluoroborate, and a pre-dispersed solute is obtained; then uniformly mixing bis (2, 2, 2-trifluoroethyl) carbonate and diethylene glycol butyl ether to serve as a solvent; heating the solvent to 45-55 DEG C, adding the pre-dispersed solute under the conditions of pulsed electric field treatment and heat-preservation stirring, carrying out heat-preservation stirring for the first time, stirring and heating to 65-75 DEG C, adding polyvinyl alcohol and the porous silicon nano material, carrying out heat-preservation stirring for the second time, carrying out microwave irradiation, standing and cooling to 20-30 DEG C, and discharging to obtain the composite material. The electrolyte can be used for preparing the aluminum electrolytic capacitor, has good high-voltage resistance, meets the current use requirements, and is good in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrolyte preparation, and specifically relates to an electrolyte for a high-voltage aluminum electrolytic capacitor and a preparation method thereof. Background Art

[0002] Aluminum electrolytic capacitor is one of the basic components of electronic products. It is a capacitor with aluminum as anode and electrolyte as cathode. Therefore, the electrolyte is the key to determining the performance of aluminum electrolytic capacitor.

[0003] With the continuous improvement of the quality of electronic products and the expansion of the application scope of aluminum electrolytic capacitors, higher requirements are put forward for their performance. Energy-saving machines such as inverters and variable-frequency air conditioners are receiving more and more attention. Aluminum electrolytic capacitors are key electronic components used for input filtering in energy-saving machines such as inverters and variable-frequency air conditioners. They are usually used in series and parallel combinations, and have very high requirements for safety and reliability. In the filter circuit, the capacitor is subjected to high voltage and high ripple current. If the power supply is unstable or overvoltage is applied, it can cause accidents such as capacitor damage, fire, and combustion. In general, the performance requirements for aluminum electrolytic capacitors are getting higher and higher. When aluminum electrolytic capacitors are in use, if a flash occurs, the electrodes will be broken down, causing the capacitor to fail, so it is of great significance to increase the flash voltage of the electrolyte.

[0004] The existing electrolytes for aluminum electrolytic capacitors can be roughly divided into the following categories:

[0005] 1. Ethylene glycol is the main solvent, and inorganic compounds such as boric acid or ammonium pentaborate are the main solutes. This type of electrolyte has low conductivity. Boric acid easily reacts with ethylene glycol to generate water at high temperature, which increases the water content in the electrolyte and the vapor pressure of the electrolyte, resulting in the capacitor valve failure.

[0006] 2. Ethylene glycol is used as the main solvent, and straight-chain hydrocarbon saturated dicarboxylic acids and their salts such as azelaic acid, sebacic acid or dodecanoic acid are used as the main solutes. The solubility of straight-chain hydrocarbons in ethylene glycol in this type of electrolyte is relatively low, the impedance of the product is large, and it is easy to generate heat, causing the solvent to volatilize, resulting in capacitor failure.

[0007] 3. The use of some branched acids or their salts, such as 2-butyl suberic acid and its salts, can improve the solubility, but the cost is high and the product performance is still not ideal, which restricts its promotion and application.

[0008] Patent application CN104167292A discloses a working electrolyte for aluminum electrolytic capacitors of electronic energy-saving lamps, and its preparation method is as follows: add 100 parts by weight of ethylene glycol to a container with a stirrer and a thermometer, start stirring, heat to 60-70°C with a closed electric heater, then add 4-8 parts by weight of hexavalent alcohol, 4-8 parts by weight of polyethylene glycol, 5-9 parts by weight of dibasic organic carboxylate ammonium, 1.5-2 parts by weight of waterproofing agent, and 0.2-0.4 parts by weight of hydrogen removal additive, heat to 120-140°C, stir and disperse at a speed of 100 rpm for 1-1.5 hours, stir until completely dissolved, stop stirring, let stand and cool to 20-30°C, and the material is obtained. The patent application uses ethylene glycol as the main solvent, hexavalent alcohol and polyethylene glycol as auxiliary solvents, dibasic organic carboxylic acid ammonium as the main solute, supplemented by waterproofing agent and hydrogen removal additives, to improve the high temperature resistance and long life requirements of the working electrolyte. However, the high voltage resistance performance of the electrolyte is still not ideal. Summary of the invention

[0009] In view of the deficiencies in the prior art, the object of the present invention is to provide an electrolyte for a high-voltage aluminum electrolytic capacitor and a preparation method thereof, which has good high-voltage resistance and meets current usage requirements.

[0010] In order to achieve the above object, the present invention adopts the following technical solution:

[0011] A method for preparing an electrolyte for a high-voltage aluminum electrolytic capacitor, the specific steps are as follows:

[0012] (1) First, acrylic acid, hydroxyethyl methacrylate, butadiene and methacrylic acid are used as monomers for polymerization reaction to obtain a polymer;

[0013] (2) then ultrasonically dispersing the polymer, mannitol and ammonium dodecanedioate in 1-hydroxyethyl-3-methylimidazolium tetrafluoroborate to obtain a pre-dispersed solute;

[0014] (3) then mixing bis(2,2,2-trifluoroethyl) carbonate and diethylene glycol butyl ether evenly to form a solvent;

[0015] (4) The solvent is heated to 45-55°C, and the pre-dispersed solute is added under pulse electric field treatment and heat preservation and stirring conditions. The solvent is stirred for the first time and heated to 65-75°C. Polyvinyl alcohol and porous silicon nanomaterials are added. The solvent is stirred for the second time and microwave irradiated. The solvent is allowed to stand and cool to 20-30°C. The solvent is discharged to obtain the electrolyte.

[0016] Preferably, in step (1), the molar ratio of acrylic acid, hydroxyethyl methacrylate, butadiene and methacrylic acid is 0.3-0.5:1.5-1.6:1:1-1.2.

[0017] Preferably, in step (1), azobisisobutyronitrile is further added as an initiator and supercritical carbon dioxide is used as a solvent to carry out a polymerization reaction; wherein the amount of azobisisobutyronitrile used is 0.02 to 0.03 times the total mass of all monomers.

[0018] Preferably, in step (1), the process conditions of the polymerization reaction are: temperature 65-75° C., introduction of carbon dioxide until the pressure reaches 15-20 MPa, and reaction time 8-10 hours.

[0019] More preferably, after the reaction is completed, the mixture is naturally cooled to room temperature, washed with deionized water for 3 to 4 times, and dried at 60 to 70° C. for 8 to 10 hours.

[0020] Preferably, in step (2), the mass ratio of the polymer, mannitol, ammonium dodecanedioate, and 1-hydroxyethyl-3-methylimidazolium tetrafluoroborate is 1:0.3-0.4:0.7-0.9:4-5.

[0021] Preferably, in step (2), the process conditions for ultrasonic dispersion are: 500-600W ultrasonic oscillation treatment for 50-60 minutes.

[0022] Preferably, in step (3), the volume ratio of bis(2,2,2-trifluoroethyl) carbonate to diethylene glycol butyl ether is 0.2-0.3:1.

[0023] Preferably, in step (4), the stirring rate is 300 to 400 r / min.

[0024] Preferably, in step (4), the process conditions of the pulse electric field treatment are: voltage 20-25V, pulse frequency 5-10Hz, duty cycle 10-20%, and maximum output current 100-150A.

[0025] Preferably, in step (4), the first heat preservation and stirring time is 30 to 40 minutes, and the second heat preservation and stirring time is 40 to 50 minutes.

[0026] Preferably, in step (4), the process conditions of microwave irradiation are: 600-700W microwave irradiation for 2-3 minutes.

[0027] Preferably, in step (4), the mass ratio of the solvent, the pre-dispersed solute, the polyvinyl alcohol, and the porous silicon nanomaterial is 100:30-40:10-12:4-7, wherein the degree of polymerization of the polyvinyl alcohol is 1500-2000.

[0028] Preferably, in step (4), the porous silicon nanomaterial is prepared by the following method: first, tetrachlorosilane and triethylamine are added to dichloromethane, stirred at room temperature (25°C) for 12 to 15 hours, magnesium silicide is added, stirred at room temperature for 8 to 10 hours, dried, subjected to high temperature treatment under an argon atmosphere, and washed to obtain the porous silicon nanomaterial.

[0029] More preferably, the molar ratio of tetrachlorosilane, triethylamine and magnesium silicide is 1:0.4:0.4; and the volume ratio of tetrachlorosilane to dichloromethane is 1:30-40.

[0030] Further preferably, the drying process conditions are: vacuum drying at 45-50°C for 3-4 hours; the high temperature treatment process conditions are: treatment at 700-800°C for 40-50 minutes; and the washing includes: washing with 1 mol / L hydrochloric acid solution for 2-3 times and washing with deionized water for 3-4 times.

[0031] An electrolyte for high-voltage aluminum electrolytic capacitor is obtained by the above-mentioned preparation method.

[0032] Application of the aforementioned electrolyte in the preparation of aluminum electrolytic capacitors.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] The present invention first uses acrylic acid, hydroxyethyl methacrylate, butadiene and methacrylic acid as monomers, and polymerizes to obtain a polymer; then the polymer, mannitol and ammonium dodecanedioate are ultrasonically dispersed in 1-hydroxyethyl-3-methylimidazole tetrafluoroborate to obtain a pre-dispersed solute; then bis(2,2,2-trifluoroethyl) carbonate and diethylene glycol butyl ether are evenly mixed to serve as a solvent; then the solvent is heated to 45-55°C, and the pre-dispersed solute is added under pulse electric field treatment and heat preservation and stirring conditions, and the mixture is stirred and heated to 65-75°C for the first time, and polyvinyl alcohol and porous silicon nanomaterials are added, and the mixture is stirred and heated for the second time, and microwave irradiated, and the mixture is left to stand and cooled to 20-30°C, and the material is discharged to obtain an electrolyte. The electrolyte can be used for the preparation of aluminum electrolytic capacitors, has good high voltage resistance, meets current use requirements, and has good application prospects.

[0035] The electrolyte of the present invention does not use boric acid substances, thus fundamentally preventing the problem of capacitor failure caused by the esterification reaction between boric acid and hydroxyl groups to generate water.

[0036] The solute of the present invention includes a polymer, ammonium dodecanedioate, etc., supplemented with mannitol, and pre-dispersed by 1-hydroxyethyl-3-methylimidazolium tetrafluoroborate. 1-hydroxyethyl-3-methylimidazolium tetrafluoroborate is an ionic liquid, which promotes the dispersion of the solute in the solvent, helps to improve the performance of the electrolyte, and improves the flash voltage and conductivity of the electrolyte.

[0037] The solvent of the present invention includes bis(2,2,2-trifluoroethyl) carbonate and diethylene glycol butyl ether. The applicant continuously screens and mixes the two in a specific ratio to achieve good dispersion of the solute.

[0038] Under the conditions of pulse electric field treatment and heat preservation and stirring, the pre-dispersed solute is added to the pre-heated solvent to promote dissolution and hydrogen bond adjustment. The present invention also adds polyvinyl alcohol and porous silicon nanomaterials to cooperate with the solute and solvent components to further improve the performance of the electrolyte. DETAILED DESCRIPTION

[0039] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Unless otherwise specified, all commodities in this invention are purchased through market channels.

[0041] Example 1

[0042] A method for preparing an electrolyte for a high-voltage aluminum electrolytic capacitor, the specific steps are as follows:

[0043] (1) First, 21.6 g (0.3 mol) of acrylic acid, 195 g (1.5 mol) of hydroxyethyl methacrylate, 54 g (1 mol) of butadiene and 86 g (1 mol) of methacrylic acid were used as monomers for polymerization reaction to obtain a polymer;

[0044] (2) Then, 0.1 kg of the polymer was ultrasonically dispersed in 0.4 kg of 1-hydroxyethyl-3-methylimidazolium tetrafluoroborate with 0.03 kg of mannitol and 0.07 kg of ammonium dodecanedioate to obtain a pre-dispersed solute;

[0045] (3) then mixing bis(2,2,2-trifluoroethyl) carbonate and diethylene glycol butyl ether in a volume ratio of 0.2:1 to form a solvent;

[0046] (4) Heat 1 kg of solvent to 45°C, add 0.3 kg of pre-dispersed solute under pulse electric field treatment and heat preservation and stirring conditions, heat preservation and stirring for the first time, stir and heat to 65°C, add 0.1 kg of polyvinyl alcohol and 0.04 kg of porous silicon nanomaterials, heat preservation and stirring for the second time, microwave irradiation, stand and cool to 20-30°C, discharge, and obtain the electrolyte.

[0047] In step (1), azobisisobutyronitrile is added as an initiator and supercritical carbon dioxide is used as a solvent to carry out a polymerization reaction; wherein the amount of azobisisobutyronitrile used is 0.02 times the total mass of all monomers.

[0048] In step (1), the process conditions of the polymerization reaction are: temperature 65°C, introduction of carbon dioxide until the pressure reaches 15 MPa, and reaction time 8 hours. After the reaction is completed, the mixture is naturally cooled to room temperature, washed with deionized water 3 times, and dried at 60°C for 8 hours.

[0049] In step (2), the process conditions for ultrasonic dispersion are: 500W ultrasonic oscillation treatment for 50 minutes.

[0050] In step (4), the stirring rate is 300 r / min.

[0051] In step (4), the process conditions of the pulse electric field treatment are: voltage 20V, pulse frequency 5Hz, duty cycle 10%, and maximum output current 100A.

[0052] In step (4), the first heat preservation and stirring time is 30 minutes, and the second heat preservation and stirring time is 40 minutes.

[0053] In step (4), the process conditions of microwave irradiation are: 600 W microwave irradiation for 2 minutes.

[0054] In step (4), the degree of polymerization of polyvinyl alcohol is 1500.

[0055] In step (4), the porous silicon nanomaterial is prepared by the following method: first, tetrachlorosilane and triethylamine are added to dichloromethane, stirred at room temperature (25°C) for 12 hours, magnesium silicide is added, stirred at room temperature for 8 hours, dried, treated at high temperature under argon atmosphere, and washed. The molar ratio of tetrachlorosilane, triethylamine, and magnesium silicide is 1:0.4:0.4; the volume ratio of tetrachlorosilane to dichloromethane is 1:30.

[0056] The drying process conditions are: vacuum drying at 45°C for 3 hours; the high temperature treatment process conditions are: treatment at 700°C for 40 minutes; and the washing includes: washing with 1 mol / L hydrochloric acid solution for 2 times and washing with deionized water for 3 times.

[0057] Example 2

[0058] A method for preparing an electrolyte for a high-voltage aluminum electrolytic capacitor, the specific steps are as follows:

[0059] (1) First, 36 g (0.5 mol) of acrylic acid, 208 g (1.6 mol) of hydroxyethyl methacrylate, 54 g (1 mol) of butadiene and 103.2 g (1.2 mol) of methacrylic acid were used as monomers for polymerization reaction to obtain a polymer;

[0060] (2) Then, 0.1 kg of the polymer was ultrasonically dispersed in 0.5 kg of 1-hydroxyethyl-3-methylimidazolium tetrafluoroborate with 0.04 kg of mannitol and 0.09 kg of ammonium dodecanedioate to obtain a pre-dispersed solute;

[0061] (3) then mixing bis(2,2,2-trifluoroethyl) carbonate and diethylene glycol butyl ether in a volume ratio of 0.3:1 to form a solvent;

[0062] (4) 1 kg of solvent is heated to 55°C, and 0.4 kg of pre-dispersed solute is added under pulse electric field treatment and heat preservation and stirring conditions. The mixture is stirred and heated to 75°C for the first time. 0.12 kg of polyvinyl alcohol and 0.07 kg of porous silicon nanomaterial are added. The mixture is stirred and heated for the second time. Microwave irradiation is performed, and the mixture is allowed to stand and cool to 30°C. The mixture is discharged to obtain the electrolyte.

[0063] In step (1), azobisisobutyronitrile is added as an initiator and supercritical carbon dioxide is used as a solvent to carry out a polymerization reaction; wherein the amount of azobisisobutyronitrile used is 0.03 times the total mass of all monomers.

[0064] In step (1), the process conditions of the polymerization reaction are: temperature 75°C, introduction of carbon dioxide until the pressure reaches 20 MPa, and reaction time 10 hours. After the reaction is completed, the mixture is naturally cooled to room temperature, washed with deionized water 4 times, and dried at 70°C for 10 hours.

[0065] In step (2), the process conditions for ultrasonic dispersion are: 600W ultrasonic oscillation treatment for 60 minutes.

[0066] In step (4), the stirring rate is 400 r / min.

[0067] In step (4), the process conditions of the pulse electric field treatment are: voltage 25V, pulse frequency 10Hz, duty cycle 20%, and maximum output current 150A.

[0068] In step (4), the first heat preservation and stirring time is 40 minutes, and the second heat preservation and stirring time is 50 minutes.

[0069] In step (4), the process conditions of microwave irradiation are: 700 W microwave irradiation for 3 minutes.

[0070] In step (4), the degree of polymerization of polyvinyl alcohol is 2000.

[0071] In step (4), the porous silicon nanomaterial is prepared by the following method: first, tetrachlorosilane and triethylamine are added to dichloromethane, stirred at room temperature (25°C) for 15 hours, magnesium silicide is added, stirred at room temperature for 10 hours, dried, treated at high temperature under argon atmosphere, and washed. The molar ratio of tetrachlorosilane, triethylamine, and magnesium silicide is 1:0.4:0.4; the volume ratio of tetrachlorosilane to dichloromethane is 1:40.

[0072] The drying process conditions are: vacuum drying at 50°C for 4 hours; the high temperature treatment process conditions are: treatment at 800°C for 50 minutes; and the washing includes: washing with 1 mol / L hydrochloric acid solution for 3 times and washing with deionized water for 4 times.

[0073] Example 3

[0074] A method for preparing an electrolyte for a high-voltage aluminum electrolytic capacitor, the specific steps are as follows:

[0075] (1) First, 21.6 g (0.3 mol) of acrylic acid, 208 g (1.6 mol) of hydroxyethyl methacrylate, 54 g (1 mol) of butadiene and 86 g (1 mol) of methacrylic acid were used as monomers for polymerization reaction to obtain a polymer;

[0076] (2) Then, 0.1 kg of the polymer was ultrasonically dispersed in 0.5 kg of 1-hydroxyethyl-3-methylimidazolium tetrafluoroborate with 0.04 kg of mannitol and 0.07 kg of ammonium dodecanedioate to obtain a pre-dispersed solute;

[0077] (3) then mixing bis(2,2,2-trifluoroethyl) carbonate and diethylene glycol butyl ether in a volume ratio of 0.2:1 to form a solvent;

[0078] (4) Heat 1 kg of solvent to 55°C, add 0.3 kg of pre-dispersed solute under pulse electric field treatment and heat preservation and stirring conditions, heat preservation and stirring for the first time, stir and heat to 75°C, add 0.1 kg of polyvinyl alcohol and 0.07 kg of porous silicon nanomaterials, heat preservation and stirring for the second time, microwave irradiation, stand and cool to 20°C, discharge, and obtain the electrolyte.

[0079] In step (1), azobisisobutyronitrile is added as an initiator and supercritical carbon dioxide is used as a solvent to carry out a polymerization reaction; wherein the amount of azobisisobutyronitrile used is 0.03 times the total mass of all monomers.

[0080] In step (1), the process conditions of the polymerization reaction are: temperature 65°C, introduction of carbon dioxide until the pressure reaches 20 MPa, and reaction time 8 hours. After the reaction is completed, the mixture is naturally cooled to room temperature, washed with deionized water 4 times, and dried at 60°C for 10 hours.

[0081] In step (2), the process conditions for ultrasonic dispersion are: 500W ultrasonic oscillation treatment for 60 minutes.

[0082] In step (4), the stirring rate is 300 r / min.

[0083] In step (4), the process conditions of the pulse electric field treatment are: voltage 25V, pulse frequency 5Hz, duty cycle 20%, and maximum output current 100A.

[0084] In step (4), the first heat preservation and stirring time is 40 minutes, and the second heat preservation and stirring time is 40 minutes.

[0085] In step (4), the process conditions of microwave irradiation are: 700 W microwave irradiation for 2 minutes.

[0086] In step (4), the degree of polymerization of polyvinyl alcohol is 2000.

[0087] In step (4), the porous silicon nanomaterial is prepared by the following method: first, tetrachlorosilane and triethylamine are added to dichloromethane, stirred at room temperature (25°C) for 12 hours, magnesium silicide is added, stirred at room temperature for 10 hours, dried, treated at high temperature under argon atmosphere, and washed. The molar ratio of tetrachlorosilane, triethylamine, and magnesium silicide is 1:0.4:0.4; the volume ratio of tetrachlorosilane to dichloromethane is 1:30.

[0088] The drying process conditions are: vacuum drying at 50°C for 3 hours; the high temperature treatment process conditions are: treatment at 800°C for 40 minutes; and the washing includes: washing with 1 mol / L hydrochloric acid solution for 3 times and washing with deionized water for 3 times.

[0089] Comparative Example

[0090] A method for preparing an electrolyte for an aluminum electrolytic capacitor, the specific steps are as follows:

[0091] (1) First, 21.6 g (0.3 mol) of acrylic acid, 195 g (1.5 mol) of hydroxyethyl methacrylate, 54 g (1 mol) of butadiene and 86 g (1 mol) of methacrylic acid were used as monomers for polymerization reaction to obtain a polymer;

[0092] (2) Then, 0.1 kg of the polymer was taken and mixed evenly with 0.03 kg of mannitol and 0.07 kg of ammonium dodecanedioate to obtain a solute;

[0093] (3) then mixing bis(2,2,2-trifluoroethyl) carbonate and diethylene glycol butyl ether in a volume ratio of 0.2:1 to form a solvent;

[0094] (4) Heat 1 kg of solvent to 45°C, add 0.3 kg of solute under pulse electric field treatment and heat preservation and stirring conditions, heat preservation and stirring for the first time, stir and heat to 65°C, add 0.1 kg of polyvinyl alcohol and 0.04 kg of porous silicon nanomaterials, heat preservation and stirring for the second time, microwave irradiation, stand and cool to 20-30°C, discharge, and obtain the electrolyte.

[0095] In step (1), azobisisobutyronitrile is added as an initiator and supercritical carbon dioxide is used as a solvent to carry out a polymerization reaction; wherein the amount of azobisisobutyronitrile used is 0.02 times the total mass of all monomers.

[0096] In step (1), the process conditions of the polymerization reaction are: temperature 65°C, introduction of carbon dioxide until the pressure reaches 15 MPa, and reaction time 8 hours. After the reaction is completed, the mixture is naturally cooled to room temperature, washed with deionized water 3 times, and dried at 60°C for 8 hours.

[0097] In step (2), the process conditions for ultrasonic dispersion are: 500W ultrasonic oscillation treatment for 50 minutes.

[0098] In step (4), the stirring rate is 300 r / min.

[0099] In step (4), the process conditions of the pulse electric field treatment are: voltage 20V, pulse frequency 5Hz, duty cycle 10%, and maximum output current 100A.

[0100] In step (4), the first heat preservation and stirring time is 30 minutes, and the second heat preservation and stirring time is 40 minutes.

[0101] In step (4), the process conditions of microwave irradiation are: 600 W microwave irradiation for 2 minutes.

[0102] In step (4), the degree of polymerization of polyvinyl alcohol is 1500.

[0103] In step (4), the porous silicon nanomaterial is prepared by the following method: first, tetrachlorosilane and triethylamine are added to dichloromethane, stirred at room temperature (25°C) for 12 hours, magnesium silicide is added, stirred at room temperature for 8 hours, dried, treated at high temperature under argon atmosphere, and washed. The molar ratio of tetrachlorosilane, triethylamine, and magnesium silicide is 1:0.4:0.4; the volume ratio of tetrachlorosilane to dichloromethane is 1:30.

[0104] The drying process conditions are: vacuum drying at 45°C for 3 hours; the high temperature treatment process conditions are: treatment at 700°C for 40 minutes; and the washing includes: washing with 1 mol / L hydrochloric acid solution for 2 times and washing with deionized water for 3 times.

[0105] Test example

[0106] The flash voltage and conductivity of the electrolytes obtained in Examples 1 to 3 and the comparative example were tested respectively.

[0107] Among them, the flash voltage is tested by TV-1CH intelligent TV tester (Yangzhou Baoou Electronics Co., Ltd.); the conductivity is tested by DDS-11A digital display conductivity meter (Shenzhen Sanli Technology Co., Ltd.), and the test temperature is 30℃.

[0108] The test results are shown in Table 1.

[0109] Table 1. Electrolyte performance test

[0110] Flash voltage (V) Conductivity (ms / cm) Example 1 652 1.95 Example 2 652 1.94 Example 3 659 1.91 Comparative Example 603 1.83

[0111] It can be seen from Table 1 that the electrolytes obtained in Examples 1 to 3 have high flash voltage, high conductivity and excellent high voltage resistance.

[0112] In the comparative example, 1-hydroxyethyl-3-methylimidazolium tetrafluoroborate was omitted, and the flash voltage and conductivity were significantly reduced, which shows that the use of 1-hydroxyethyl-3-methylimidazolium tetrafluoroborate as an ionic liquid is directly related to the dissolution of the solute in the solvent, thereby affecting the performance of the electrolyte.

[0113] The present invention illustrates the technical concept of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of individual raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing an electrolyte for a high-voltage aluminum electrolytic capacitor, characterized in that: The specific steps are as follows: (1) First, acrylic acid, hydroxyethyl methacrylate, butadiene and methacrylic acid are used as monomers for polymerization reaction to obtain a polymer; (2) then ultrasonically dispersing the polymer, mannitol and ammonium dodecanedioate in 1-hydroxyethyl-3-methylimidazolium tetrafluoroborate to obtain a pre-dispersed solute; (3) then mixing bis(2,2,2-trifluoroethyl) carbonate and diethylene glycol butyl ether evenly to form a solvent; (4) The solvent is heated to 45-55°C, and the pre-dispersed solute is added under pulse electric field treatment and heat preservation and stirring conditions. The solvent is stirred for the first time and heated to 65-75°C. Polyvinyl alcohol and porous silicon nanomaterials are added. The solvent is stirred for the second time and microwave irradiated. The solvent is allowed to stand and cool to 20-30°C. The solvent is discharged to obtain the electrolyte.

2. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of acrylic acid, hydroxyethyl methacrylate, butadiene and methacrylic acid is 0.3-0.5:1.5-1.6:1:1-1.

2.

3. The preparation method according to claim 1, characterized in that: In step (1), azobisisobutyronitrile is added as an initiator and supercritical carbon dioxide is used as a solvent to carry out a polymerization reaction; wherein the amount of azobisisobutyronitrile used is 0.02 to 0.03 times the total mass of all monomers.

4. The preparation method according to claim 1, characterized in that: In step (1), the process conditions of the polymerization reaction are: temperature 65-75° C., introduction of carbon dioxide until the pressure reaches 15-20 MPa, and reaction time 8-10 hours.

5. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the polymer, mannitol, ammonium dodecanedioate, and 1-hydroxyethyl-3-methylimidazolium tetrafluoroborate is 1:0.3-0.4:0.7-0.9:4-5; The process conditions of ultrasonic dispersion are: 500-600W ultrasonic oscillation treatment for 50-60 minutes.

6. The preparation method according to claim 1, characterized in that: In step (3), the volume ratio of bis(2,2,2-trifluoroethyl) carbonate to diethylene glycol butyl ether is 0.2-0.3:

1.

7. The preparation method according to claim 1, characterized in that: In step (4), the stirring rate is 300-400 r / min.

8. The preparation method according to claim 1, characterized in that: In step (4), the process conditions of the pulse electric field treatment are: voltage 20-25V, pulse frequency 5-10Hz, duty cycle 10-20%, and maximum output current 100-150A; The first heat preservation and stirring time is 30 to 40 minutes, and the second heat preservation and stirring time is 40 to 50 minutes; The process conditions of microwave irradiation are: 600-700W microwave irradiation for 2-3 minutes; The mass ratio of the solvent, the pre-dispersed solute, the polyvinyl alcohol, and the porous silicon nanomaterial is 100:30-40:10-12:4-7, wherein the degree of polymerization of the polyvinyl alcohol is 1500-2000; The porous silicon nanomaterial is prepared by the following method: firstly, tetrachlorosilane and triethylamine are added into dichloromethane, stirred at room temperature for 12 to 15 hours, magnesium silicide is added, stirred at room temperature for reaction for 8 to 10 hours, dried, treated at high temperature under argon atmosphere, and washed to obtain the porous silicon nanomaterial.

9. An electrolyte for a high voltage aluminum electrolytic capacitor, characterized in that: The invention is obtained by the preparation method according to any one of claims 1 to 3.

10. Use of the electrolyte according to claim 9 in the preparation of aluminum electrolytic capacitors.